Pengembangan Model Pembelajaran Kewirausahaan Berbasis Proyek untuk Menumbuhkan Motivasi Berwirausaha - Fitri Rahmawati; Arif Susanto (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Students as pioneers of nation development, must be able to grow and create jobs through developing an entrepreneurial spirit in higher education. The aims of this research are (1) to develop a project-based entrepreneurship learning model and (2) to test the effectiveness of the project-based entrepreneurship learning model to foster students' entrepreneurial motivation in the Primary School Teacher Education Study Program (PGSD) Muhammadiyah University, Purworejo. The method used in the research is the Research & Development model DBR (Design Based Research). The research subjects were 36 students of the PGSD Study Program at Muhammadiyah University Purworejo studying Local Business entrepreneurship. Data were collected using observation, portfolio, questionnaire, interview and FGD methods. The data analysis techniques used in this research are qualitative analysis, percentages, and difference tests (t-test). The research results show that: 1) improvements to the Local Business entrepreneurship learning model are more directed at applicable practicum, and creating graduates who have an entrepreneurial spirit; 2) design and prototype development consists of three components, namely learning objectives, learning methods, and assessment; 3) validation tests and limited tests show that the learning objectives, material content and presentation are in accordance with the content, appearance and language; and 4) product testing using an experimental class determined based on student learning styles, the majority of students have an accommodating learning style, the results of the portfolio assessment show students have very good and good grades, the products produced by student work groups are in accordance with learning styles, and effectiveness tests show The application of project-based Local Business entrepreneurship learning in the PGSD Study Program at Muhammadiyah University, Purworejo, is able to foster students' entrepreneurial spirit very well.